MODERN DATA ON PAPILLOMA VIRUS INFECTION, AND OPPORTUNITIES OF ITS PROPHYLAXIS - I.S. Tarasov (Voprosy Sovremennoj Pediatrii, 2009)
This article analyzes questions of quadrivalent vaccine Gardasil use for the protection of human papilloma virus (HPV) type 6, 11, 16, and 18, responsible to 70% of carcinoma of uterine cervix cases, and 90% of anogenital condylomas. The results of wide ranging trials show that vaccine is effective in almost 100% of cases for the prevention of pre oncological intraepithelial dysplasia of uterine cervix, vulva, and vagina, anogenital condylomas, caused by vaccine types of HPV. Studies describe vaccine's high immunogenicity and safety. The vaccine was included in immunizations schedule in many countries. Obtained data give us hope that vaccination against uterine cervix cancer will be included in Russian National immunizations schedule in the immediate future.Key words: human papilloma virus, carcinoma of uterine cervix, quadrivalent vaccine.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):35-41)